Bridging chains mediate nonlinear mechanics of polymer nanocomposites under cyclic deformation. (18th June 2020) - Varol, H. Samet; Srivastava, Anchit; Kumar, Sachin; Bonn, Mischa; Meng, Fanlong; Parekh, Sapun H.
Abstract: Elastomer-based nanocomposites, mixtures of elastomeric rubber with hard nanoparticles, generally exhibit strain stiffening under large strains while also showing strain softening at low strain during large cyclic deformations due to the Mullins Effect. Numerous studies have documented the Mullins effect over the last 50 years, and many models have been developed to explain (and predict) the Mullins effect as it is closely related to material failure. Even with this rich history, relatively few studies have connected experimentally measured changes in nanocomposite chain structure with nonlinear strain hardening and nanofiller dispersion. In this work, we quantify the strain hardening mechanics, and chain anisotropy in situ in silica-filled acrylonitrile butadiene rubber (NBR) nanocomposites under cyclic tensile loading. Macroscopic strain hardening and molecular chain anisotropy increased after the first loading cycle, as a strong Mullins effect appeared, for nanocomposites with sufficient filler volume fraction. In composites with low filler content, we observed little increase in strain hardening or chain anisotropy and a barely-visible Mullins effect. Our results provide strong experimental support that chain delamination from the filler surface is related to the Mullins effect in nanocomposite materials. Graphical abstract: Image 1 Highlights: In situ mechano-chemical (Raman) spectroscopy allows quantification of mechanics and chain anisotropy in nanocomposites. Nanocomposites with sufficient fillers show strain hardening and chain anisotropy that increase after the first loading cycle. Cyclic loading of silica/NBR nanocomposites with non-specific filler-matrix interaction does not affect filler dispersion. Chain slippage from filler surfaces and subsequent alignment with cyclic loading coincides with the Mullins effect.